Efektifitas Program Pencegahan Stunting Melalui Peningkatan Gizi Bayi Dan Balita di Puskesmas Rhee - Marlina; Siti Atika Rahmi; Rahmat Hidayat (Lembaga Bale Literasi, 2026)
This study uses a qualitative research type, namely a research method used to examine natural object conditions. where the researcher is the key instrument. The data collection technique used was triangulation or a combination. Data were collected through observation, interviews, documentation. Data analysis through data reduction, data presentation, drawing conclusions or verification. The study concluded that the effectiveness of the stunting prevention program through improving infant and toddler nutrition at the Rhee Community Health Center has been quite good, due to the integrated approach starting from pregnancy, providing regular health services, and intensive education to the community. These efforts include monitoring child growth and development at the Integrated Health Post (Posyandu), an exclusive breastfeeding and nutritious complementary feeding program, and education on the importance of balanced nutrition and sanitation. Barriers to the effectiveness of the stunting prevention program through improving infant and toddler nutrition at the Rhee Community Health Center include low levels of community knowledge and economic status, ineffective parenting patterns, lack of access to nutritious food, lack of support and appreciation for Posyandu cadres, and suboptimal coordination between programs and the availability of nutrition experts.